Fluxos de calor e transferência de energia calorífica entre o oceano e a atmosfera sobre estruturas oceânicas de mesoescala no Atlântico Sul - Arsego, Diogo Alessandro (2012)
Understanding the interactions between ocean and atmosphere in regions of oceanographic fronts is of vital importance for the improvement of numerical models for weather and climate forecasting. In the South Atlantic Ocean (SAO) the meeting between the warm waters of the Brazil Current (BC) and the cold waters of the Malvinas (Falkland) Current (MC) in the region known as the Brazil-Malvinas Confluence (BMC), results in intense mesoscale oceanic activity and, for this reason, this region is considered one of the most energetic of the Global Ocean. The interactions resulting from the thermal contrast in regions oceanographic fronts of the OAS are investigated in this work through estimates of heat fluxes based on data collected in situ and by satellite. The results of this study show that the response to the thermal contrasts found in the ocean is in the form of heat fluxes and these fluxes are critical in modulating the atmospheric boundary layer (ABL). Estimation based on data collected in situ show that in the warm side (north) of the oceanographic front the fluxes are more intense (latent heat: 62 W/m² and sensible heat: 0.6 W/m²) than in the cold side (south) (latent heat: 5.8 W/m² and sensible heat: -13.8 W/m²). In the South Atlantic Current (SAC) along the 30° S parallel, heat fluxes are directly related to the meandering characteristic of the current. The data collected in situ, in addition to allow heat flux estimates at a better spatial resolution, were used to develop a new method for estimating the heat energy exchanged between the atmosphere and the ocean caused by the presence of mesoscale oceanic structures. This methodology consists in the comparison of a radiosonde profile taken over waters of the structure of interest and another taken over waters which do not belong to this structure. The methodology was used to estimate the heat energy transfer between the atmosphere and the ocean over the top of three structures sampled in the OAS. The estimation of the heat energy transferred by a warm eddy detached from the BC points to an energy in the latent (sensible) form of 1.6 1017 J (-2.8 1016 J) which corresponds to approximately 0.011 % of the total heat energy of the eddy transferred to the atmosphere during the field experiment and 0.78 % transferred during the supposed lifetime of the eddy (3 months). Along the CSA two oceanic structures were studied: (i) a cold meander that receives from the atmosphere energy in the latent (sensible) form of 1.4 106 J/m2 (5.4 105 J/m2), and (ii) warmer waters associated with a detached eddy from the Agulhas Current (AC) that transfer to the atmosphe heat energy of approximately 4 106 J/m2 an 5.7 106 J/m2 in the latent and sensible forms, respectively. The estimation of heat energy transfer on top of mesoscale oceanic structures clearly demonstrate the importance of these structures for the heat exchanges between the ocean and the atmosphere and must be taken into account in future works about this subject in the SAO.